Clinical evaluation of knowledge and attitude among garments dust induced bronchial asthma in tertiary care hospitals in Coimbatore zone. - MUTHUKUMAR .A; SUNDARAGANAPATHY .R (International Journal of Pharma and Bio Sciences, 2018)
Patient education is one of the important factors that influencing for proper management of asthma. Patients should have knowledge in their etiology, usage of medication regarding asthma. Assessment of disease knowledge and attitude is crucial for the patient’s health improvements and wellbeing as well as preventing them from asthma complications. In India, there is a scarcity of data regarding disease knowledge and drug adherence within the occupational asthma. Hence this cross sectional study was conducted in textile industry to access disease knowledge and attitude among asthmatic patients in Coimbatore city. During this study all the required information had been taken out of 1157 patients yielding response at the rate of 100%. The majority of the participants about 99% were between 30 and 60 years of age. The ratio of male were 64.91% and female were 35.09%. The maximum value of disease knowledge was 20 and 54% and attitude score was 15 and 43%. The present clinical study has been demonstrated that the patients had lack of knowledge and medication adherence with prescribed regimen that may result in to misconceptions on disease management, especially in patients suffering from work related asthma.